Intellectual Profile of Adolescents with Headache: A Case–Control Study Using the WISC-IV - Chiappedi, Matteo; Mensi, Martina; Antonaci, Eliana; Zavani, Elena; Tronconi, Livio; Termine, Cristiano; Balottin, Umberto (Frontiers in Neurology, 2018)
There are few literature evidences about the intellectual profile of adolescents with headache and no study has used the fourth edition of the Wechsler Intelligence Scale for Children (WISC-IV) in patients with a diagnosis of headache according to the ICDH-III-beta. We recruited 30 patients (age 11-14 years; male: female = 1: 2) seen for headache in a tertiary center in Northern Italy and 30 healthy controls matched for age and sex, recruited in a public school from the same geographic area. The diagnosis of headache was done according to the ICHD-III criteria (beta version): the case group was composed of 16 patients with migraine and 14 with tension-type headache. Cognitive functioning was assessed using the WISC-IV. Recruited patients with idiopathic headache diagnosis had on average a cognitive function within the normal range. We found no statistically significant differences in the total Intellective Quotient comparing patients with headache and controls; the Working Memory index was however lower in patients with headache (p = 0.012) and in particular we found a lower Digit Span (p <0.001). We also found a borderline statistical difference (p = 0.051) between case and controls CVI (Verbal Comprehension Index), which was due to a lower score in the Similarities subtest (p <0.001). Our results suggest that, although within normal limits, cognitive functioning of adolescents with headache differs from that of healthy peers regarding memory and verbal skills. The Working Memory Index is related to the subject's ability to store new information and keep them in short-term memory, to maintain focused attention and to manipulate them to find solutions. The difference in Similarities is also important because it provides a measure of the level of verbal reasoning and concept formation; it is also a measure of verbal abstract thinking skills relevant for language development, lexical knowledge, auditory comprehension, memory and ability to discriminate between essential and non-essential characteristics. Our data, in keep with previous findings, suggest the need for further researches in order to better understand the pathogenesis of these difficulties and obtain ideas for an adequate rehabilitative treatment.